Educational research - public responsibility, private funding? - Palle Rasmussen (Taylor & Francis Group, 2021)
Like other Nordic countries, Denmark is a mixed-economy welfare society, where capitalist production and market logics coexist with public policy having social cohesion and equality as important priorities. Educational and pedagogical research, which is a main knowledge base for policy and practice in schools and the education system, is also seen as a field of public responsibility, carried out mainly in universities and other public research institutes. In recent years, however, a number of private actors have engaged in funding research related to education and learning. The actors include private organizations doing research in connection with product development and privately established foundations initiating research and development projects. The interplay between public and private funding and management can promote quality research combining new general knowledge with societal relevance; but it can also lead to narrow criteria for topics and methods, unsettling important balances in the field of educational research. The article examines and discusses these developments, especially the role of private foundations, as well as the conditions for fruitful interaction between the public sector and private actors in educational research.